2008
DOI: 10.1038/labinvest.3700707
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiles of gastric carcinoma characterized by quantitative DNA methylation analysis

Abstract: Transcriptional silencing by CpG island hypermethylation is a potential mechanism for the inactivation of tumor-related genes. Virtually, all types of human cancers show CpG island hypermethylation, and gastric carcinoma (GC) is one of the tumors with a high frequency of aberrant CpG island hypermethylation. In this study, we prescreened DNA methylation of 170 CpG island loci in a training set of 8 paired GC and GC-associated non-neoplastic mucosae (GCN) using MethyLight technology and selected 27 DNA methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 35 publications
3
111
0
1
Order By: Relevance
“…35 The gene with the highest correlation between methylation and expression was CHFR (checkpoint with forkhead and ring finger domains gene), an E3 ubiquitin ligase critically involved in a mitosis checkpoint that prevents errors during chromosome segregation. In a previous study, methylation of CHFR was observed in 39% of the gastric cancers and loss of CHFR expression was associated with sensitivity of gastric cancer cells to microtubule NGS methylation analysis in gastric carcinogenesis inhibitors, 34 although this association has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…35 The gene with the highest correlation between methylation and expression was CHFR (checkpoint with forkhead and ring finger domains gene), an E3 ubiquitin ligase critically involved in a mitosis checkpoint that prevents errors during chromosome segregation. In a previous study, methylation of CHFR was observed in 39% of the gastric cancers and loss of CHFR expression was associated with sensitivity of gastric cancer cells to microtubule NGS methylation analysis in gastric carcinogenesis inhibitors, 34 although this association has been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is one of the epigenetic phenomena that occur at the molecular level involving regulation of cell of development and differentiation, aging, and diseases (Shaw, 2006;Supic, et al, 2009). Notably, most of the gene inactivation mechanism involved in cancer progression is the promoter hypermethylation of CpG islands (Kang et al, 2007;Noushmehret al, 2010). This process is now widely recognized as either a causative or correlative event in carcinogenesis (Herman and Baylin, 2003;Jones, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of gastric carcinoma (GC) is highest in Eastern Asia, Eastern Europe, and South America while the lowest rates are in Africa and North America [140,141]. During cancer development, aberrant CpG island hypermethylation is found to occur frequently in the stomach [142].…”
Section: Gastric Cancermentioning
confidence: 99%